2004
DOI: 10.1142/s0218539304001579
|View full text |Cite
|
Sign up to set email alerts
|

A Software Reliability Growth Model With Testing Effort Dependent Learning Function for Distributed Systems

Abstract: Effective software process improvement will not start until management insists that product development work be planned and properly managed. This becomes even more challenging in an increasing number of major system developments made up from distributed sub-system software projects. These sub-systems are integrated and validated to provide the final system and product release. The need is growing to estimate, risk assess, plan and manage the development of these distributed sub-systems and the final full syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 9 publications
0
15
0
Order By: Relevance
“…The proposed model is motivated by the work of Kapur et al [11] and Pachauri et al [12]. In this section, a Software Reliability Growth Model based on Non Homogenous Poisson Process (NHPP) is developed by incorporating two things, one is the testing effort and second one is dynamic fault.…”
Section: Model Demonstrationmentioning
confidence: 99%
See 2 more Smart Citations
“…The proposed model is motivated by the work of Kapur et al [11] and Pachauri et al [12]. In this section, a Software Reliability Growth Model based on Non Homogenous Poisson Process (NHPP) is developed by incorporating two things, one is the testing effort and second one is dynamic fault.…”
Section: Model Demonstrationmentioning
confidence: 99%
“…The present study considered a growth model incorporating test effort and dynamic faults. A number of Software Reliability Growth Models have been constructed with or without testing effort [1][2][3][4][5][6][7][8][9][10][11][12]. Kapur et al [11] proposed Software reliability growth model with testing effort dependent learning function.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are many papers that discuss the problems of considering and estimating the amount of testing-effort (TE) consumption during software testing (Kapur et al, 2004(Kapur et al, , 2006Huang and Kuo, 2002;Huang, 2005;Yamada et al, 1993). For example, Musa et al (1987) showed that execution time is a better exposure indicator for software reliability modeling than calendar time.…”
Section: Introductionmentioning
confidence: 99%
“…A testing effort function (TEF) describes the distribution of TE (CPU time, manpower, etc) during the testing period. Putnam et al, 11 Yamada et al, 12,13 Bokhari and Ahmad, 14 Kapur et al, 15 Kuo et al 16 and Huang et al 17,18 proposed SRGM describing the relationship among the testing time, TEC and the number of software faults detected. Most existing SRGM belong to exponential-type models.…”
Section: Introductionmentioning
confidence: 99%